2007
DOI: 10.1039/b710759e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient co-sensitization of nanocrystalline TiO2 films by organic sensitizers

Abstract: Dye-sensitized solar cells based on co-sensitization of organic dyes having complementary spectral absorption in the visible region resulted in a panchromatic response, which exhibited 86% incident monochromatic photon-to-current conversion efficiency in the visible region; the optimized cell gave a short circuit current density of 15.5 mA cm(-2), an open circuit voltage of 685 mV and a fill factor of 0.70 corresponding to an overall conversion efficiency of 7.43% under solar simulated light irradiation of 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
134
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(136 citation statements)
references
References 12 publications
(10 reference statements)
0
134
0
2
Order By: Relevance
“…A large body of research has been conducted to enhance the light harvesting efficiency in TiO 2 photoanodes. In this context, the development of more efficient dye sensitizers, including organic dyes with a higher extinction coefficient 5,6 and energy-relay dyes, 7 and their effective utilization methods, such as cocktail dye 8,9 and selective dye adsorption 10,11 concepts, have prevailed. In addition, the introduction of a scattering layer and inverse opal nanostructures are also common.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has been conducted to enhance the light harvesting efficiency in TiO 2 photoanodes. In this context, the development of more efficient dye sensitizers, including organic dyes with a higher extinction coefficient 5,6 and energy-relay dyes, 7 and their effective utilization methods, such as cocktail dye 8,9 and selective dye adsorption 10,11 concepts, have prevailed. In addition, the introduction of a scattering layer and inverse opal nanostructures are also common.…”
Section: Introductionmentioning
confidence: 99%
“…Yum et al have demonstrated efficiencies of 7.43% and respectable absorbances in the red/near IR region using cells cosensitized with JK2 and SQ1, both organic, non-porphyrin molecules ( Figure 8). JK2 and SQ1 have impressive molar absorption coefficients of 4.2 x 10 4 M -1 cm -1 at 452 nm and 15.9 x 10 4 M -1 cm -1 at 636 nm, respectively (Yum et al, 2007). Advanced dye engineering has produced superior organic dyes.…”
Section: Fully Organic Dyesmentioning
confidence: 99%
“…Additionally, they have a large molar extinction coefficient in the red-shifted region 18,26,29,36,37 or around 400 nm to compensate for the light-harvest loss by electrolytes (I…”
Section: -39mentioning
confidence: 99%
“…Many co-sensitization systems have been proposed and demonstrated improved photovoltaic performance, such as ruthenium complex co-sensitized with an organic dye, 17-26 porphyrin 27-30 or phtalocyanine [31][32][33][34] co-sensitized with an organic dye, and organic dye co-sensitized with another organic dye. [35][36][37][38][39][40] The co-sensitizers generally have a suitable molecular structure to avoid competitive adsorption and effectively suppress dye aggregation.…”
Section: Introductionmentioning
confidence: 99%